PERMAINAN PLASTISIN UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK KELAS B TK CAHAYA KASIH MODAYAG: PLASTICINE GAMES TO IMPROVE FINE MOTOR SKILLS OF GRADE B CHILDREN AT CAHAYA KASIH MODAYAG KINDERGARTEN - Watulingas, Hellen F; Wantah, Mario Erick (Universitas Islam Malang, 2021)
The problem encountered at Cahaya Kasih Modayag Kindergarten is the lack of stimulating teachers for children to relax plasticine by squeezing, flattening, feeling, grinding in their fingers. The purpose of this study was to apply plasticine games by forming houses to improve fine motor skills in children at Cahaya Kasih Modayag Kindergarten. The research method is classroom action research (PTK). The subjects of this study were 13 children. The results of the discussion in the first cycle of research were: (31%) because children were able to move their fingers in flattening plasticine. Meanwhile (8%) because there is an increase in the radius. And (61%) because children experience delays in moving their fingers. Then the researcher continued the second cycle (76%) because the child was able to relax. Meanwhile (24%) because the child is able to move his fingers so that it becomes an airplane shape.